EKSISTENSI DA'WAH HALAL CORNER MELALUI INSTAGRAM DALAM MEMAHAMKAN PRODUK HALAL PADA FOLLOWERSNYA - Siti Nur Fadlilah; Siti Uswatun Hasanah (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2025)
This research aims to find out the existence of Halal Corner through Instagram in understanding halal products to its followers. The method used in this study uses a qualitative descriptive method. The results of the analysis found about the Existence of Da'wah Halal Corner Through Instagram in Understanding Halal Products to Followers are by running the da'wah program such as showing how to find halal products, introducing products that need to be watched out, recommending halal products, providing consulting services, and offline da'wah. The conclusion is the results of the research used functional structural theory, namely functional analysis with the concepts of function, dysfunction and role-set. It was found that the Halal Corner da'wah through Instagram has been proven to exist and has a manifest function whose existence has a positive impact on the social situation in cyberspace or netizens, especially to its followers in understanding halal products through the Halal Corner da'wah program which continues to be carried out in a patterned and repetitive manner and is always up to date on the Halal Corner Instagram account and da'wah activities both online and offline. It was also found that da'wah Halal Corner has a latent function, which can indirectly strengthen social ties between followers who feel they have the same values and goals in using and consuming halal products. It was also found that Halal Corner has limitations within its internals that can be dysfunctional to other facts in social situations in cyberspace and the real world. Also da'wah Halal Corner has many roles (role- sets) including as an educator, as a curator of halal product content, as a social activist, and as a liaison with halal authorities.